Essays on Monetary Policy, Inflation, and Income Distribution - Matamoros Romero, Guillermo Rufino (Université d'Ottawa / University of Ottawa, 2023)
This dissertation is divided into three distinct chapters looking at the theoretical and empirical relationship between monetary policy, inflation, and income distribution in industrialized countries. The first chapter investigates the effect of monetary policy on the income share of workers at the industry level in Canada and the United States. The second chapter studies the relationship between firms' markups and inflation during the 2021-22 inflation surge in select industrialized countries. The third chapter assesses the Taylor-rule framework of monetary policy with regards to an estimated central bank reaction function for several industrialized countries, analyzing its potential effects on the rentier income share over time. This dissertation makes several contributions to the economic literature, particularly in the field of post-Keynesian empirical macroeconomics.
Keywords: Monetary Policy; Income Distribution; Inflation; Post-Keynesian Economics